Il rinnovo della composizione della Corte costituzionale slovacca a margine delle elezioni presidenziali del 2019, tra dinamiche coabitazioniste e riforma dei meccanismi di selezione dei giudici costituzionali (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2019)
In January 2018, the Government started debating on the reform of constitutional judges’ selection mechanism. The Slovak National Council proved to be able to introduce minor changes to the first phase of constitutional judges’ selection process, through the adoption of Act no. 314/2018. However, the rejection of constitutional amendment bill no. 1060, on October 23, 2018, represented a missed opportunity to reform the Constitutional Court. The inability to find a compromise among different political forces, in fact, paved the way to a new confrontation between the President of the Republic and the National Council on the subject.